Cover Feature: Robotic Catalysis: A High‐Throughput Method for Miniature Screening of Mesoporous Metal Oxides (Chemistry ‐ Methods 4/2021). Issue 4 (1st April 2021) - Potgieter, Kariska; Aimon, Anthony; Smit, Elize; von Delft, Frank; Meijboom, Reinout
Abstract : The Cover Feature shows that a high‐throughput method was developed for the screening of up to 96 mesoporous metal oxide catalysts. This system was created by employing robotics such as an acoustic liquid handler for the miniature catalyst formation and 3D printing. This proof of concept shows that mesoporous metal oxide could be miniaturised by the deposition of nanodroplet on a glass plate and screened for their activity in the oxidation of morin as a model reaction. More information can be found in the Full Paper Kariska Potgieter et al .